STATUS DAN PERAN PEREMPUAN DALAM NOVEL BELENGGU KARYA ARMIN PANE: REFLEKSI DAN OBSESI [Status and Role of Women in The Belenggu Novel Armin Pane's Works: Reflection and Obsession] - Ninawati Syahrul (TOTOBUANG, 2020)
The problem  studied in this study was how the status and role of women were reflected in the  Shackles’ novel? What weree the causes of problems?  how were to solve the problems experienced by women solved? This study aimed to describe and interpret the problems experienced by women related to their role in the review of feminism. This study uses a qualitative interpretive method of interpretation with a feminist approach. Analysis data came from the  literature study,the narrative text, and inter-figure dialogue in the novel Shackles. Data collection technique in the form of literature study by listening and recording the main issues e decomposed. Data analysis techniques used narrative analysis s. The results showed: First, the role of women was still limited to public and domestic space, such as as managers of women's organizations in public and the  household in domestic. Second, the issue of gender construction  harmed women. Third, the issue of women as the cause of differences in patriarchal culture  benefited men and gender construction. This issues also placeed women under dignity or not in line with men. Fourth the faint and subdued attitude of women to the problems  faced by escaping ?the messing life. Masalah yang ingin dikaji dalam penelitian ini adalah bagaimana status dan peran perempuan yang terefleksi dalam novel Belenggu? Apa penyebab permasalahan ?  bagaimana cara menyelesaikan permasalahan yang dialami oleh perempuan? Penelitian ini bertujuan untuk mendeskripsikan dan menginterpretasikan permasalahan yang dialami oleh perempuan terkait dengan perannya dengan tinjauan feminisme. Penelitian ini menggunakan metode deskriptif kualitatif interpretatif dengan pendekatan feminisme. Data analisis berasal dari studi pustaka, yakni  berupa teks narasi dan dialog antartokoh dalam novel Belenggu. Teknik pengumpulan data berupa studi pustaka dengan cara menyimak dan mencatat pokok persoalan yang akan diurai. Teknik analisis data menggunakan teknik analisis naratif. Hasil penelitian menunjukkan: Pertama, peran perempuan masih sebatas ruang publik dan domestik, seperti sebagai pengurus organisasi perempuan di bidang publik dan sebagai ibu rumah tangga di bidang domestik . Kedua, persoalan konstruksi gender yang merugikan pihak perempuan. Ketiga, permasalahan perempuan sebagai akibat perbedaan budaya patriarki yang menguntungkan laki-laki dan konstruksi gender yang menempatkan perempuan di bawah harkat atau tidak sejajar dengan laki-laki. Keempat, sikap perempuan yang lemahdan takluk terhadap permasalahan yang dihadapi dengan cara melarikan diri dari kemelut kehidupan.